2021
DOI: 10.21037/jtd-21-1004
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram model for early postoperative hyperlactatemia in patients undergoing cardiac surgery

Abstract: Background:Postoperative hyperlactatemia (POHL) is common in patients undergoing cardiac surgery, associated with adverse outcomes. The aim of this study was to identify predictors for POHL after cardiac surgery and to develop and validate a predictive model. Methods:Adult patients who underwent open heart surgery at our institution between 2016 and 2019 were retrospectively included. The patients were randomly divided into training and validation groups at a 2:1 ratio. Multivariate logistic regression was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Similar to other studies, 6,22,3234 the multivariate analyses identified the STS score, logistic Euro SCORE II, durations of aortic cross-clamping, CPB, anaesthesia, and surgery, intraoperative myocardial ischemia, and cumulative intraoperative bleeding as predictors for hyperlactatemia. Additionally, similar to previous investigators, 14,17 several independent predictors for vasoplegia after CPB have been identified in the present study, including long durations of aortic cross-clamping and CPB, intraoperative episodes of hypotension and myocardial ischemia, and the need for PRBCs transfusion.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to other studies, 6,22,3234 the multivariate analyses identified the STS score, logistic Euro SCORE II, durations of aortic cross-clamping, CPB, anaesthesia, and surgery, intraoperative myocardial ischemia, and cumulative intraoperative bleeding as predictors for hyperlactatemia. Additionally, similar to previous investigators, 14,17 several independent predictors for vasoplegia after CPB have been identified in the present study, including long durations of aortic cross-clamping and CPB, intraoperative episodes of hypotension and myocardial ischemia, and the need for PRBCs transfusion.…”
Section: Discussionsupporting
confidence: 90%
“…Weiss and Rady et al reported that emergency surgery correlated significantly with time to extubation and lung injury, and was independent predictor of early postoperative pulmonary dysfunction ( 27 , 28 ). Previous studies have identified the close relationship between renal insufficiency and various postoperative complications after cardiovascular surgery, such as hypoxemia, pneumonia, hyperlactatemia, and tracheostomy ( 3 , 29 33 ). Although the related researches on the relationship between renal insufficiency and hypoxemia are limited and the exact mechanisms remain to be further investigated, we guess that inflammatory responses, erythropoietin production by the kidney, and the subsequent oxygen delivery may be involved ( 34 ).…”
Section: Discussionmentioning
confidence: 99%